The Future of Creating Jobs for Vietnamese Workers after Covid-19 Pandemic - Ha, Dao Ngoc; Huong, Nguyen Thi Thu; Anh, Nguyen Tuan (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The picture of the global economy has experienced a tumultuous year with "dark colours" as the dominant colour due to the severe impact of the Covid-19 pandemic. In December 2020, a vaccine against the acute respiratory infection Covid-19 was released to help control the pandemic and restore economic activity. The world economy has shown significant signs of recovery. Hence, the International Labour Organization (ILO) said that the labour market has begun to recover after unprecedented disruptions caused by the Covid-19 pandemic in 2020. However, the negative impact of the pandemic is still ongoing. The organization’s Covid-19 Impact Report provides the latest figures showing that global working hours in 2020 have decreased by 8.8% compared to Q4 2019. This decline includes the number of working hours reduced for those still employed and those who lost their jobs. Notably, about 71% of people who lost their jobs (equivalent to 81 million people) decided to leave the labour market instead of looking for another job and becoming unemployed (GSO, 2021). This article focuses on analyzing the current situation of job creation for Vietnamese workers after Covid-19, pointing out the achieved results, limitations, causes and some recommendations to promote job creation for Vietnamese workers in the post-Covid-19 context.